Curricular Territory: Defining Flexibility as a Transversal Principle of the Geography Curriculum at UCR (Revista Electrónica Calidad en la Educación Superior, 2023)
The curricular flexibility, considered as a transversal principle in the design, evaluation, and management of a curriculum, must be defined through a collective process, combining the interpretations of curriculum stakeholders (students, teachers, administrators, among others) with associated theoretical features. Therefore, a definition is presented, constructed through the development of a discussion workshop, informed by literature review, aimed at generating a standardized concept regarding the understanding, practice, and requirements for curricular flexibility. As a result, in addition to proposing a definition, the specificities of the learning environment in which the Bachillerato y Licenciatura en Geografía curriculum is developed, taught at the Escuela de Geografía at the Universidad de Costa Rica, are highlighted, enabling the operationalization of criteria and mechanisms to demonstrate flexibility.
Keywords: Curricular flexibility; Curriculum; Professional education; Higher education